2018
DOI: 10.1017/ice.2018.196
|View full text |Cite
|
Sign up to set email alerts
|

Effect of copper-impregnated linens on multidrug-resistant organism acquisition and Clostridium difficile infection at a long-term acute-care hospital

Abstract: Copper-impregnated surfaces and linens have been shown to reduce infections and multidrug-resistant organism (MDRO) acquisition in healthcare settings. However, retrospective analyses of copper linen deployment at a 40-bed long-term acute-care hospital demonstrated no significant reduction in incidences of healthcare facility-onset Clostridium difficile infection or MDRO acquisition.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(25 citation statements)
references
References 12 publications
0
25
0
Order By: Relevance
“…The key outcome measures reported across the studies included consumption of targeted antimicrobials and/ or associated costs 112,113,132,[114][115][116][117]122,123,128,131 , incidence of Clostridium difficile 112,113,[123][124][125]127,[114][115][116][117][119][120][121][122] or incidence and/ resistance rates of Klebsiella pneumoniae 128,129,144,[130][131][132][133][134]137,139,143 as well as risk on other HCAIs 114,121,123,127,130,137,139 . Additional outcomes included containment of an outbreak of the targeted organisms 135,136,138,[140][141][142]…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The key outcome measures reported across the studies included consumption of targeted antimicrobials and/ or associated costs 112,113,132,[114][115][116][117]122,123,128,131 , incidence of Clostridium difficile 112,113,[123][124][125]127,[114][115][116][117][119][120][121][122] or incidence and/ resistance rates of Klebsiella pneumoniae 128,129,144,[130][131][132][133][134]137,139,143 as well as risk on other HCAIs 114,121,123,127,130,137,139 . Additional outcomes included containment of an outbreak of the targeted organisms 135,136,138,[140][141][142]…”
Section: Discussionmentioning
confidence: 99%
“…32.4% (11) of the studies were conducted in the United States of America 115,118,141,146,[119][120][121][122]124,126,127,136 whereas two studies each are based in Canada 112,114 and Greece 135,137…”
Section: Characteristics Of Selected Studiesmentioning
confidence: 99%
See 2 more Smart Citations
“…More importantly, several studies [23,39,42,[44][45][46][47][48][49] conducted with antimicrobial medical textiles (mostly medical textiles containing copper oxide), with exception of one study, demonstrated a significant reduction of HAIs in the study arm using the antimicrobial medical textiles (Figure 2). While additional studies may be needed to better understand the effect of antimicrobial medical textiles and reduction of HAIs in different medical settings, the described studies in Figures 1 and 2 overall have given significant support to the notion that biocidal textiles used in clinical settings may be an important adjunct in the fight against HAIs.…”
mentioning
confidence: 99%

Antimicrobial Textiles

Krishnaraj,
Gokarneshan,
Jothimanikandan
et al. 2024
SDGs and Textiles